SEMIOTIC ANALYSIS OF LINGUISTIC LANDSCAPES: ARABIC LANGUAGE PHENOMENA IN MALANG CITY PUBLIC SPACE - Muhammad Farihul Qulub; Ismatul Khasanah (El-Jaudah : Jurnal Pendidikan Bahasa dan Sastra Arab, 2024)
Abstract: Terms derived from foreign languages are no longer strange things in people's lives in urban areas. Terms in foreign languages are increasingly spreading and perched in language markers in public spaces such as public infrastructure, shop signage, signage of an inn business. This study aims to determine the phenomenon of life of the people of Malang City who have Arab characteristics, who have an interesting background because of the Arab Ethnic Community. This use of Arabic in linguistic and semiotic landscapes has something to do with cultural patterns and the perspective of the people of Malang City towards the use of Arabic to be maintained. Linguistic and semiotic landscapes are used to study Arabic elements found in public spaces in Malang, East Java. Descriptive qualitative methods were used in this study to describe the results of the analysis conducted on the data. The data used is in the form of interviews that summarize the mindset and perspective of the community towards Arabic used in public spaces. From this study, 16 data from 3 sectors were found, including: (1) Education Sector, (2) Culinary Sector and (3) Economic Sector. These three emerge that the use of Arabic in the linguistic landscape of Malang City shows the function of symbols and the function of information. In addition, the semiotic pattern finds that there is a public mindset towards using Arabic naming is considered more unique, fashionable and has more selling points because the more unique the name or sign will be more attractive to the community even though people do not fully understand the meaning of naming in these various sectors.